Estudio de factibilidad técnico financiera del levantamiento artificial de un pozo del campo Castilla mediante el análisis nodal a partir del uso de un programa especializado (2017)
In this work of degree will be carried out a technical feasibility study of the artificial lifting of a well of the field Castilla by means of the nodal analysis from the use of a specialized program, for this reason it is described mainly the generalities of the field Castilla, its History, location, geological framework and production history.